Education Evidence Approach: Type Validity of Computer Based Test (CBT) In Formative and Summative Assessment for Vocational High Schools - Rais Amin; Sri Rahayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to provide some guidelines for SMK to choose the right type of CBT. Advances in adult technology that are now increasingly rapidly have led to new breakthroughs in the national education system in Indonesia. Pandemic outbreak current Covid-19, the government and institutions engaged in education are now starting to take steps again to develop and improve the concept of distance assessment. One of them is the Computer Based Test (CBT) which is a technology in assisting the implementation of the assessment using an online. Handling and developing tests carried out remotely using a digital system at Vocational High Schools (SMK). This study distinguishes CBT into three different types, namely linear tests, automated tests, and computed adaptive tests. So that in the search and consideration in selecting CBT it is necessary to be guided by the purpose of the test in question. The test approach can determine which goals can be achieved using a particular test. The discussion of this study focuses on two different test approaches, namely the formative test assessment approach and the summative test assessment approach. The suitability of each type of CBT in measuring the performance of different test approaches was evaluated based on three test characteristics, namely the purpose of the test, the duration of the test, and the computerized adaptive test. This study aims to provide some guidelines in selecting the appropriate type of CBT for use in SMK.